Financial Recordkeeping Training for SMEs to Enhance Business Transparency and Accountability in Central Cikarang SMEs - Fuadi, Agus; Wulandari, Tirin; Wulandari, Dian Sulistyorini; Rahman, Ibra Fatur (Jurnal Pengabdian Pancasila (JPP), 2024)
This paper presents the implementation of a training program titled "Financial Recordkeeping Training for SMEs to Enhance Business Transparency and Accountability in Central Cikarang." The primary aim of the program was to improve the financial management practices of small and medium enterprises (SMEs) in the Cikarang Pusat area by enhancing their knowledge of financial recordkeeping, transparency, and accountability. The training covered key topics such as basic bookkeeping techniques, the preparation of financial statements, and the role of transparency in sustaining business operations. The program was assessed using the Three Box Method, categorizing participants' understanding into three levels: Low, Medium, and High. The results showed that most participants achieved a medium level of proficiency, indicating a moderate improvement in their financial management capabilities. A smaller group of participants demonstrated a high level of proficiency, suggesting they were able to effectively implement the new practices in their businesses. This paper concludes that the training successfully improved participants' financial literacy and contributed to better business transparency and accountability.